The relationship of platelet to lymphocyte ratio with the presence and extent of coronary atherosclerosis detected by coronary computed tomography angiography - Çakır, Hakan; Toprak, Cüneyt; Karagoz, Ali; Uysal, Samet; Havan, Nuri; Kuzeytemiz, Mustafa; Kaymaz, Cihangir; Demir, Mehmet (The European Research Journal, 2022)
Objectives: Platelet-lymphocyte ratio (PLR) combines the predictive risk of platelet and lymphocyte counts into a single risk index. PLR has been studied as a predictive marker in a variety of cardiovascular diseases. However, our understanding of the link between PLR and coronary artery disease (CAD) remains limited. The present study aimed to evaluate the relationship between PLR and intensity of coronary atherosclerosis in patients with suspected CAD. Methods: In this retrospective study, we included 221 patients undergoing dual-source 64-slice coronary computed tomography angiography (CCTA). Total and different types of leukocyte counts were measured with an automatic blood counter. Based on a modified version of the American Heart Association’s categorisation, the coronary artery tree was divided into 16 segments. To assess the extent of coronary atherosclerosis, the number of affected coronary segments was counted. Coronary artery plaques were classified into three categories: (1) calcified plaque, (2) non-calcified plaque, and (3) mixed plaque. Results: After multivariable backward stepwise regression analysis, PLR remained as an independent predictor for both the presence and extent of coronary atherosclerosis (OR=2.38, 95% CI: 1.27-4.47 and OR=1.66, 95% CI: 1.10-2.51, respectively). There was no significant relationship between PLR and plaque morphology. Conclusions: Higher PLR was associated with the intensity of coronary atherosclerosis detected by CCTA. Further research is necessary to determine the optimal approach to using PLR in medical practice.